2022
DOI: 10.3390/ijerph19052978
|View full text |Cite
|
Sign up to set email alerts
|

Hand Hygiene Compliance at Two Tertiary Hospitals in Freetown, Sierra Leone, in 2021: A Cross-Sectional Study

Abstract: Hand hygiene actions are essential to reduce healthcare-associated infections and the development of antimicrobial resistance. In this cross-sectional study at two tertiary hospitals, Freetown, Sierra Leone, we observed hand hygiene compliance (defined as using handwash with soap and water or alcohol-based hand rub (ABHR) amongst healthcare workers between June and August 2021. Using the WHO Hand Hygiene tool, observations were made in relation to the type of opportunity, different wards and types of healthcar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 27 publications
(48 reference statements)
2
23
0
Order By: Relevance
“…Toraman et al (2009) found the overall average handwashing rate of health personnel to be 73%, while the distribution occurred as 86% for nurses, 56% for the physicians, and 72% for the assistant health personnel. Similar to our study, the handwashing habits of doctors are at a lower rate (Al-Maani et al, 2022;Duman-Karakuş, Tanyel, and Deveci, 2022;Kamara et al, 2022).…”
Section: Fear Of Covidsupporting
confidence: 88%
See 2 more Smart Citations
“…Toraman et al (2009) found the overall average handwashing rate of health personnel to be 73%, while the distribution occurred as 86% for nurses, 56% for the physicians, and 72% for the assistant health personnel. Similar to our study, the handwashing habits of doctors are at a lower rate (Al-Maani et al, 2022;Duman-Karakuş, Tanyel, and Deveci, 2022;Kamara et al, 2022).…”
Section: Fear Of Covidsupporting
confidence: 88%
“…Prior to our study, we did not investigate support structures such as adequate hospital availability of hand hygiene products, hand hygiene posters/reminders, or healthcare worker leadership, or employee perceptions such as fatalism, all of which may have influenced the a very weak, positive relationship. As a matter of fact, it has been revealed in a study that hand hygiene compliance is different at various levels of the health system and it is known that research is needed to learn more about compliance (Kamara et al, 2022). Across countries and time, levels of handwashing adherence and strictness of policies were high.…”
Section: Fear Of Covidmentioning
confidence: 99%
See 1 more Smart Citation
“…Hand hygiene practices among healthcare workers -An audit conducted in a tertiary care hospital in the central province of Sri Lanka highly inadequate especially during the pandemic, where maintaining good HH was of utmost importance. Our total HH compliance was very similar to observations made in studies done in Sri Lanka, Sierra Leone, Southwest Nigeria and Ghana (17,29,30,31). The moment1, "bef-pat."…”
Section: Auditsupporting
confidence: 87%
“…This finding was supported by other studies. 17,28,[33][34][35][36] Training is an effective tool to increase the knowledge about hand hygiene actions for the prevention of nosocomial infections. 37 Training is essential to enhance awareness of microbial transmission by hands, emphasize the importance of hand hygiene and its indications, and demonstrate the correct procedures for hand rubbing and hand washing.…”
Section: Discussionmentioning
confidence: 99%